The social field of migrant smuggling and the self-designation of Mexican migrant smugglers - Izcara-Palacios, Simón Pedro (2025)
There is a certain consensus in the academic community on the need to establish a terminological differentiation between the different actors involved in migrant smuggling due to the existence of a correlation between the semantic values of the terms used to designate migrant smugglers and the social field of facilitation of irregular migration. The aim of this research is to examine whether the migrant smugglers interviewed referred to themselves with different terms depending on the degree of hierarchy of the networks in which they participated, the geographical origin of the migrants they transported, and the sex and activity of the latter. This research is based on a qualitative methodology. Qualitative interviews were conducted with 36 Mexican migrant smugglers integrated into networks of different degrees of hierarchy, transporting migrants with different geographical origins, sexes and activities. The term used by most of the interviewees to refer to their activity was that of pollero. Likewise, the different degree of hierarchy, geographical origin, sex and activity of the migrants transported by human smugglers did not correlate with the terms with which the interviewees called themselves. We conclude that the non-differentiation in the lexicon used to name those who facilitate irregular border crossing allows the damage caused by border control policies to be attributed to states, rather than to migrant smugglers.